Improving Large Taxpayers' Compliance : A Review of Country Experience - Benon, Olivier (Occasional Papers; Occasional Paper ;, 2002)
One area that has not been reviewed in developing countries is the growing focus on different segments of the taxpayer population-including the large taxpayers-as a way to encourage greater stability in public revenue flows, improve the effectiveness and efficiency of tax administration, and introduce innovations in the public sector. Based on a sample of about 40 countries, this paper provides an overview of country practices in terms of the organization, systems, and procedures used by tax administrations to monitor the compliance of the large taxpayers. The paper also reviews the effectiveness of large taxpayer operations in selected developing and transition countries where the IMF has recommended their establishment.